A Critical Assessment of Turkish Islamic Feminism: A Simone de Beauvoirian Perspective - Kanatli, Mehmet (Journal of Muslims in Europe, 2022)
From the early years of the Turkish Republic to the end of the 1990s, the individuals who constitute the Turkish Islamic feminist movement have been the ‘other’ to Kemalist secular women. In the mid-2000s, having found a solution to the ‘headscarf question’, Muslim women started to express their demands, ranging from equal opportunities in education to the transformation of patriarchal structures and the reconstruction of female identity. The article’s main objective is to develop arguments for how dilemmas can be transcended in the process of identity-building. The main hypothesis put forward is that the participants in the Turkish Islamic feminist movement, who could turn their dilemmas into advantages if they managed to establish their relationship with the ‘other’ in line with the universal secular values of equality and freedom, will achieve their existential freedom only to the extent that they are able to act from an existential perspective.